Why ASEAN is Cooperating in the Education Sector? - Jan Gawron (IKAT: The Indonesian Journal of Southeast Asian Studies, 2017)
Over the last few years ASEAN member states have begun collaborating more tightly in the tertiary education sector, which has led to a cooperation agreement with the European Union to help harmonize and lift the overall standard of tertiary education in the region. However, the broader question is - why is that the case? Education is not considered a classical field of regional integration, and this chapter seeks to analyze various sources - which include references from elitist circles, as well as the public sphere - in order to identify the motivation for cooperation in the education sector through qualitative content analysis. The analysis is based on a theoretical framework, which incorporates both a neofunctionalist approach and a norm diffusion approach which show that the predominant factors behind this cooperation process are economic.